Discharge Handoff Communication and Pediatric Readmissions. Issue 1 (1st January 2017) - Coller, Ryan J.; Klitzner, Thomas S.; Saenz, Adrianna A.; Lerner, Carlos F.; Alderette, Lauren G.; Nelson, Bergen B.; Chung, Paul J.
Abstract : BACKGROUND: Improvement in hospital transitional care has become a major national priority, although the impact on children's postdischarge outcomes is unclear. OBJECTIVE: To characterize common handoff practices between hospital and primary care providers (PCPs), and test the hypothesis that common handoff practices would be associated with fewer unplanned readmissions. DESIGN, SETTING, AND PATIENTS: This prospective cohort study enrolled randomly selected pediatric patients during an acute hospitalization at a tertiary children's hospital in 2012‐2014. MEASUREMENTS: Primary care and patient data were abstracted from administrative, caregiver, and PCP questionnaires on admission through 30 days postdischarge. The primary outcome was 30‐day unplanned readmission to any hospital. Logistic regression assessed relationships between readmissions and 11 handoff communication practices. RESULTS: We enrolled 701 children, from which 685 identified PCPs. Complete data were collected from 84% of PCPs. Communication practices varied widely—verbal handoffs occurred rarely (10.7%); PCP notification of admission occurred for 50.8%. Caregiver experience scores, using an adapted Care Transitions Measure‐3, were high but were unrelated to readmissions. Thirty‐day unplanned readmissions to any hospital were unrelated to most handoff practices. Having PCP follow‐up appointments scheduled prior to discharge was associated with more readmissions (adjusted odds ratio, 2.20; 95% confidence interval, 1.08‐4.46). CONCLUSION: Despite their presumed value, common handoff practices between hospital providers and PCPs may not lead to reductions in postdischarge utilization for children. Addressing broader constructs like caregiver self‐efficacy or social determinants is likely necessary.